Xanthorrhizol contents, α-glucosidase inhibition, and cytotoxic activities in ethyl acetate fraction of Curcuma zanthorrhiza accessions from Indonesia - Nurcholis,Waras (2018)
ABSTRACT Curcuma zanthorrhiza Roxb., Zingiberaceae, a species from Indonesia with xanthorrhizol as the major metabolite, has been used as a folk medicine in several of pharmacological activities. This work aimed to evaluate the xanthorrhizol contents, α-glucosidase inhibition, and cytotoxic activities in ethyl acetate fraction from accessions of C. zanthorrhiza. High-performance liquid chromatography investigated xanthorrhizol content with the standard. Pharmacological activities were evaluated by inhibition of α-glucosidase, the brine shrimp lethality test, and anticancer activity. The ethyl acetate fraction yield varied from 8.24% (Karanganyar) to 13.13% (Sukabumi). The xanthorrhizol contents were found to be in the range 43.55% to 47.99% with Ngawi and Wonogiri promising accessions having the lowest and highest value, respectively. IC50 value for α-glucosidase inhibition ranged from 339.05 µg/ml (Karanganyar) to 455.01 µg/ml (Ngawi). LC50 value for cytotoxic activities ranged from 33.25 µg/ml (Ngawi) to 42.28 µg/ml (Karanganyar) in brine shrimp lethality test, 3.10 µg/ml (Karanganyar) to 9.85 µg/ml (cursina-III) in Vero cell, and 1.17 µg/ml (Ngawi) to 6.83 µg/ml (Sukabumi) in MCF-7 cell. In this study, C. zanthorrhiza accessions have a high in xanthorrhizol contents and cytotoxic activities that showed a high potential of studied accessions for breeding programs on a commercial scale.